The R563Q Mutation of the Beta Subunit of the Epithelial Sodium Channel: Prevalence and Effect - Jones, Dr Erika Sherad Wilshire (Department of Medicine, 2014)
Hypertension is a major worldwide predictor of morbidity and mortality. The search for genes that contribute to blood pressure is ongoing. The epithelial sodium channel genes were implicated when the beta subunit (SCNN1B, gene ID 6338) was found to have a mutation that caused Liddle's syndrome. The R563Q mutation in the beta subunit has been associated with hypertension and pre-eclampsia in the Xhosa and Coloured people in Cape Town. The thesis consists of a cross-sectional analysis of the prevalence of the R563Q mutation in multiple ethnic groups in South Africa and a longitudinal functional assessment in response to saline infusion. The objectives were to determine the prevalence of the R563Q mutation and association with hypertension, and if it persists within families; to speculate as to the origins of the mutation; to determine if there were any relevant clinical differences between comparable patients with essential hypertension; to determine if the mutation predicted a difference in response to acute sodium loading and if a physiological difference is observed in sodium channel activity when expressed in oocytes. 8 A high frequency of hypertensives in Johannesburg and Cape Town were found to be heterozygous and the mutation associated with hypertension, including within families. In the Khoisan the R563Q mutation was found at a high frequency (19%) in a random sample, suggesting the mutation originated from this population. The saline challenge illustrated the in vivo effects of the mutation. The results suggest that the sodium channel is innately overactive in heterozygous subjects and that counter-regulatory mechanisms are in place to compensate for changes in renal sodium handling. However, preliminary in vitro testing in oocytes did not show a difference in sodium channel activity. Conclusion: This thesis has shown that the R563Q mutation is found in multiple ethnic groups in South Africa, in which it associates with hypertension; and possibly originated from the Khoisan. In vivo effects are described. The results are important because hypertension resulting from the R563Q mutation is a common and treatable cause of hypertension. It is recommended that hypertension units in South Africa screen for the mutation and alter treatment appropriately. A further recommendation is that a sodium channel inhibitor, such as amiloride, in an appropriate form, is registered in South Africa for the treatment of hypertension.